The Meaning of The Phrase The March 2020 Issue of Kompas Newspaper and Implication in Indonesian Language Learning - Soleh Ibrahim (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
Kompas Newspaper article published in March 2020 is a few newspaper articles discussing the figure of inpirative, social society, health, politics and law, history, and education. The article on the news is interesting to study the types of meanings because it relates to the Indonesian language learning materials Senior High School program. This research aims to (1) study the meaning of phrases in the newspaper text of Kompas March 2020 and (2) know the implications of newspaper texts with Indonesian language learning materials in high school. This research is done by a descriptive method. The descriptive method in this study is to describe the phenomenon of linguistic as it is. The data analysis technique used is a method of data analysis involving the approach (theory) as a research data analysis tool. So, the language research method includes the methods and techniques of data collection that is used by language speakers, and the data analysis methods and techniques that will be found in the linguistic rules according to the use of the language itself in the society of its said. The results of this study can be explained that the meaning of the phrase in the newspaper text Kompas edition of March 2020 and implications of the meaning of the phrase in the newspaper text Kompas March 2020 edition with learning materials in Senior High School.